Rekoreografi tari kiprah lengger karya peni priyono: Sebagai upaya pelestarian budaya pendhalungan - Diah Syavira Mutihan; Retnayu Prasetyanti Sekti (Universitas Negeri Surabaya, 2026)
This study aims to describe the concept and process of the re-choreography of the Kiprah Lengger Dance created by Peni Priyono as an effort to preserve Pendhalungan traditional arts in Probolinggo City. This research is motivated by the process of condensing and restructuring the Kiprah Lengger Dance while maintaining its identity, characteristics, and cultural values. This study employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. This research applied Jacqueline Smith’s (1985) construction method theory to analyze the re-choreography process and the choreography concepts consisting of unity, variation, repetition, contrast, sequence, climax, balance, and harmony to examine the concept of the Kiprah Lengger Dance.The results of the study indicate that the concept of the rechoreography of the Kiprah Lengger Dance remains grounded in the spirit of preserving traditional arts by maintaining the essence, characteristics, and identity of the dance. Based on the analysis of choreography concepts, the Kiprah Lengger Dance demonstrates elements of unity, variation, repetition, contrast, sequence, climax, balance, and harmony that form a cohesive choreographic structure. Furthermore, based on Jacqueline Smith’s construction method theory, the re-choreography process was carried out through stages of dance stimuli, motif development, and the restructuring of choreographic forms. The re-choreography was realized through the selection and condensation of movements, simplification of repetitive sections, integration of similar movement motifs, and adjustment of the performance structure to make it more effective and communicative. The result of the re-choreography is a performance that is more concise and efficient while still preserving the aesthetic values, characteristics, and cultural spirit inherent in the Kiprah Lengger Dance.Keywords: rechoreography, movement condensation, Kiprah Lengger Dance, Pendhalungan, preservation of traditional art.